Pemberdayaan Masyarakat Dalam Perilaku Ibu Primigravida Trimester III Terhadap Teknik Menyusui Yang Benar di Kelurahan Ladang Bambu Kecamatan Medan Tuntungan - Widia Astuti Tanjung; Karsana Karsana (Journal of Community Development, 2022)
Breast milk is one of the perfect and best foods for babies because it contains the nutritional elements needed by babies and is very beneficial for the baby's growth and development. Breastfeeding is one way to provide the best nutrition for babies and strengthen the bond between mother and baby. Breast milk contains immune-forming antibodies which can help fight viral bacteria so that breastfed babies are at less risk of developing diseases such as: diarrhea, asthma, allergies, ear infections, respiratory tract infections, constipation, sudden infant death syndrome and meningitis. The aim of this health education for community empowerment is to increase the knowledge of TM III pregnant women about the importance of exclusive breastfeeding. The method used in this counseling is by presenting material using lecture and demonstration methods using communication media such as leaflets. The number of respondents was 12 people, carried out on October 18 2023. Pretest and posttest were carried out to evaluate the mother's knowledge before and after counseling. The results of the evaluation of mothers' knowledge before the counseling was carried out showed that 5 people (20%) were in the good category and there was an increase in mothers' knowledge to 12 people (88%) after the counseling was in the good category.